CISSP : complete video course - Greene, Sari Stern, 1957- (LiveLessons (Indianapolis, Ind.), 2015)
CISSP Complete Video Course contains 24 hours of training with content divided into 9 lessons with 94 video sub-lessons. The videos consist of live trainer discussions, screencasts, animations, and live demos. The video lessons in this course review each exam objective so you can use this course as a complete study tool for taking the CISSP exam. Instruction throughout offers detailed explanations, demos, tips, and more.